CEO Reputation and Market Reactions in Indonesia - Minda Utami, Eristy; Henry Wijaya, John; Amaliawati, Lia (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the impact of CEO turnover in companies in the 2011-2017 period on listed companies. This study focused on abnormal returns of shares of companies listed on the Stock Exchange that experienced CEO turnover during 2011-2017. This abnormal return change is thought to be stimulated by the CEO turnover announcement. The successor CEO’s reputation was also suspected to have affected market reaction. The abnormal return examined here is the average abnormal return and cumulative average abnormal return. Sample withdrawal uses purposive sampling with a total of 17 companies and Mann Whitney different tests. The results show that investors tend to be negative towards CEO turnover as indicated by abnormal returns which tend to be negative after CEO turnover, besides that there is no difference in performance both before and after the CEO turnover followed by no difference in stock returns.